2020
DOI: 10.1002/ajb2.1531
|View full text |Cite
|
Sign up to set email alerts
|

Life history variation in an invasive plant is associated with climate and recent colonization of a specialist herbivore

Abstract: Spatial variation in selective pressures can lead to intraspecific variation in life history, favoring some life histories and constraining others depending on the vulnerability of life stages. We examined how spatial variation in herbivory and climate influences flowering size and the occurrence of semelparity (reproducing once) versus iteroparity (reproducing multiple times) in the introduced range of an invasive plant, houndstongue (Cynoglossum officinale). Houndstongue is a short-lived, semelparous perenni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
(123 reference statements)
0
3
0
Order By: Relevance
“…This "Neolithic Plant Invasion Hypothesis" (NPIH) could explain why many European species are problematic in agropastoral ecosystems all over the world. Some examples are Cynoglossum officinale L., and Linaria vulgaris Mill., which are invasive in the United States (Duncan and Williams, 2020;Blatt et al, 2022;Gaskin et al, 2022) and can be found in the archaeobotanical record, e.g., from well features in central Europe dating back to the Early Neolithic (Herbig et al, 2013). Independent of the exact native origin of invaders, gathering empirical evidence for a role of pre-adaptation to agropastoral practices in invasions has become an important goal in invasion ecology.…”
Section: Pre-adaptation To Anthropogenic Disturbance Could Favor Plan...mentioning
confidence: 99%
“…This "Neolithic Plant Invasion Hypothesis" (NPIH) could explain why many European species are problematic in agropastoral ecosystems all over the world. Some examples are Cynoglossum officinale L., and Linaria vulgaris Mill., which are invasive in the United States (Duncan and Williams, 2020;Blatt et al, 2022;Gaskin et al, 2022) and can be found in the archaeobotanical record, e.g., from well features in central Europe dating back to the Early Neolithic (Herbig et al, 2013). Independent of the exact native origin of invaders, gathering empirical evidence for a role of pre-adaptation to agropastoral practices in invasions has become an important goal in invasion ecology.…”
Section: Pre-adaptation To Anthropogenic Disturbance Could Favor Plan...mentioning
confidence: 99%
“…Similarly, differences in fecundity of the intentionally introduced, but now considered invasive, red king crab (Paralithodes camtschaticus) were seen across three fjords in Norway (Hjelset 2012). These differences can be a result of interactions with other species, such as in the invasive houndstongue (Cynoglossum officinale) where interactions with an introduced herbivorous beetle decreased flowering size and thus the proportion of plants that were iteroparous (Duncan and Williams 2020). Alternatively, reproduction can differ as a result of environmental conditions, as in the invasive bivalve Xenostobus securis, where the timing of gametogenesis in the invaded range, but not in the native range, is triggered by temperature and therefore differs across invaded sites with local temperature variation (Montes et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Natural enemies (such as parasitic plants and phytophagous animals) are one of the key factors affecting plant life history (Duncan and Williams, 2020;Huang et al, 2021). In the process of plant growth, natural enemies obtain nutrients and water by directly parasitizing or feeding on the stems, leaves, flowers, fruits, and other organs of the plant, subsequently impacting the photosynthetic rate of the host plant, thereby affecting the growth and development of the host plant, among other life history characteristics (Zhong et al, 2021;Min-Yao et al, 2022;Velasco Cuervo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%